Rancang Bangun Alat Perontok Kacang Tanah - Lukman Prayugo; Mega Ayu Yusuf; Parjono Parjono (Musamus AE Featuring Journal, 2023)
The process of threshing peanut pods in Merauke Regency is generally done manually without using tools. The average area of ​​land cultivated by peanut farmers is less than ¾ hectare, while the post-harvest process of peanuts, especially during the process of threshing peanut pods, requires quite a lot of energy and time. The peanut pod thresher on the market has dimensions of 2200 mm x 70 mm x 1300 mm with a capacity of 307 kg of pods per hour. So it does not suit the needs of peanut farmers. Therefore, machines are needed that are suitable for peanut farmers in Merauke Regency. The method used is designed by changing the dimensions to 690 mm x 520 mm x 860 mm and the size of the threshing eye is smaller. The results of testing the peanut thresher tool showed that the effectiveness of shelling tests for 2 kg and 4 kg samples was 95.71% and 89.75%, respectively. The capacity of the machine using a 4 kg test sample is smaller compared to testing using a 2 kg sample, namely 129 kg/hour and 153.8 kg/hour respectively. The resulting capacity is linear with threshing effectiveness. So this modified peanut threshing machine can be an alternative for peanut farmers in Merauke because it can be used by small-scale farmers.